Effects of liming and potassium fertilization on sweet sorghum grown in a Dark-Red Latosol - Rosolem, C. A.; Machado, J. R.; Coleta, O. Della; Marcondes, D. A. S. (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was set on a Dark-Red Latosol sandy phase (loamy sand) to study the effects of 0, 2, 4, 6 and 8 t/ha of lime, in presence or not of 100 kg/ha of K2O. The experiment was conducted during two years, with the potassium being reapplied, and without liming. In the first year there was an interaction of lime and potassium. The stalk yields were increased by liming up to 2 t/ha in the absence of potassium fertilizer but when potassium was applied the yields of sweet sorghum stalks were increased by doses up to 4 t/ha of lime. There was an increase in grain production due to liming up to 2 t/ha, but there was not any effect of potassium fertilization. In the second year there was a linear response of stalk yields to liming and the application of 100 kg/ha of K2O caused an increase in stalk production. There was not any effect of treatments upon juice quality.